Analytical Study of Country Risks Affecting the Flow of Investments of Foreign Oil Companies to the Syrian Oil Sector. (Journal of Hama University, 2020)
The study examined the risk of foreign oil companies’ investment in Syrian oil sector. The used indicators reflect the level of exposure in the context of the size of the investments, and the risks of the business environment. The ultimate objective is to verify the existence of a long-term balance between the risk factors and the volume of foreign investments flowing into the Syrian oil sector, using economic analysis and standard tests.The researcher analyzed the risk factors and their economic grades, which affect investment decision making. Also, he studied the factors that stimulate the flow of foreign direct investment into the oil sector, then tested the standard stability of the time series of the search variables, and modeled a standard model in the dynamic least squares (DOLS).The results show a significant and long-term balance relation between the studied risk factors and the decline in the volume of oil investments. So, it is necessary to overcome the risk factors and create a good investment climate that attracts oil investment companies, especially for friendly countries, allowing the provision of the right conditions and encouraging for an investment activity on the basis of right sustainable development.